Transition management in urban neighbourhoods: The case of Carnisse, Rotterdam, the Netherlands. - Wittmayer, Julia M.; Steenbergen, Frank van; Bach, Matthew (Springer, 2018)
The case study in this chapter marks a socially disadvantaged community in the South of Rotterdam, the Netherlands: Carnisse. Transition management was applied in Carnisse in the context of decreasing public service provisions, closing of public facilities, high unemployment and crumbling social cohesion to facilitate the self-organisation of inhabitants to address persistent sustainability problems. This chapter illustrates how the process implementation has been influenced by political, institutional and emotional factors related to the place-specific characteristics of urban neighbourhood transitions. While urban neighbourhoods mark opportunities for self-organisation - through for example emotional connectedness - the political playing field can provide support, or restrain it. The transition management application in Carnisse shows several advantages of applying transition management on the scale of an urban community. It provided a new perspective for the development of that community, increased social capital, supported reflexivity on roles and own behaviours and revealed opportunities for self-organisation.
Keywords: Stadtentwicklung; Stadtquartier; Stadtumbau; Nachhaltige Stadtentwicklung; Öffentlichkeitsbeteiligung; Akteur